Altered lumbo-pelvic-hip complex muscle morphometry and contraction change in postpartum pelvic girdle pain and asymptomatic subjects: a cross-sectional study - Lin, Ziling; Hou, Yanjun; Chen, Xueling; Liu, Yanping; Wang, Xiangbin (Frontiers in Physiology, 2025)
ObjectiveLumbo-pelvic-hip complex muscle training is considered a crucial component of exercise rehabilitation for postpartum women with pelvic girdle pain (PGP). However, there is a paucity of research evidence regarding the morphological changes and contraction function of these muscles in postpartum women with PGP. Understanding the alterations in lumbo-pelvic-hip complex muscles function associated with PGP, is crucial for tailoring effective rehabilitation strategies and promoting optimal postpartum recovery. Therefore, this study aims to compare the differences in muscle thickness and contraction function of lumbo-pelvic-hip complex muscle between postpartum women with PGP and asymptomatic controls using ultrasound imaging.MethodsOne hundred and fifty postpartum women with PGP and fifty age-matched asymptomatic postpartum women were recruited in this study. Real-time musculoskeletal ultrasound was utilized to measure the resting muscle thickness of nine lumbo-pelvic-hip complex muscles, including the erector spinalis (ES), latissimus dorsi (LD), quadratus lumbalis (QL), gluteus maximus (GMax), gluteus medius (GMed), piriformis (PF), iliacus muscle (IM), rectus femoris (RF), and biceps femoris (BF). The thickness of the GMax, GMed, RF, and BF muscles were measured at maximum contraction to calculate a contraction: rest ratio.ResultsCompared to the asymptomatic women, those with PGP exhibited reduced resting thickness of the ES and GMax muscles bilaterally, as well as increased resting thickness of the right LD and IM muscles. Furthermore, the PGP group demonstrated decreased thickness of the left GMed and right RF muscles at maximum contraction. The contraction ratio was also diminished for the GMax muscles bilaterally, left GMed, and right RF in women with postpartum PGP. Conclusion: Postpartum women with PGP demonstrated reduced thickness, asymmetry, and diminished contractility of the lumbo-pelvic-hip complex muscles. Exercise prescriptions for postpartum women with PGP should incorporate targeted strengthening of the ES, GMax, GMed, and RF muscles.ConclusionPostpartum women with PGP demonstrated reduced thickness, asymmetry, and diminished contractility of the lumbo-pelvic-hip complex muscle. Exercise prescriptions for postpartum women with PGP should incorporate targeted strengthening of the ES, GMax, GMed, and RF muscles.